Welding Deformation Prediction and Control for a Stiffened Curved Panel–Cylindrical Shell Hybrid Structure - Bo Wang; Chao Wang; Xuchen Liu; Junan Yi; Zhen Chen; Ao Wang (Journal of Marine Science and Engineering, 2025)
Numerical simulation of the welding process is critical for predicting and controlling structural deformation. Previous numerical studies have predominantly focused on investigating the welding deformation of simple structures. However, actual engineering structures in naval architecture, aerospace, and construction applications exhibit significantly greater complexity. This study develops a finite element–based numerical approach to analyze the welding deformation in a stiffened curved panel–cylindrical shell hybrid structure. The connection between the stiffened curved panel and the cylindrical shell is achieved through a multi-pass welding procedure. The welding efficiency is enhanced through a segmented moving heat source model, which offers measurable practical benefits in engineering implementation. Furthermore, two useful strategies are proposed to mitigate the welding deformation, namely the utilization of welding sequence optimization and the applications of mechanical constraints. The results demonstrate an over 20% reduction in the out-of-plane deformation of the stiffened curved panel and more than 30% in the radial deformation of the cylindrical shell. It is indicated that the presented numerical approach can serve as a practical tool for the welding process optimization of complex welded structures.